2018
DOI: 10.1111/mcn.12656
|View full text |Cite
|
Sign up to set email alerts
|

Orange Fanta versus orange fruit: A novel measure of nutrition knowledge in Malawi

Abstract: This paper introduces a novel survey instrument to identify distinct components of nutrition knowledge and test for links between knowledge and dietary choices in Southern Malawi. Our first aim is to distinguish respondents' familiarity with recommended behaviours, such as when to start breastfeeding or introduce solid foods, from respondents' factual knowledge about mechanisms, such as whether biscuits or papaya and orange fruit or orange Fanta contribute more to future health. We find knowledge of nutrition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Importantly, we also observed that dyads with overweight children were more likely to purchase special foods for children and spend more money on these special foods. Previous studies found that Malawian parents in rural areas have a preference for packaged foods, like biscuits, Kamba puffs (a packaged snack food), and orange soda, over less processed, more nutrient dense alternatives [ 59 62 ]. Together with our findings, this suggests that behavior change communication interventions targeting feeding of “junk” foods to young children could be important for tackling the obesity epidemic in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we also observed that dyads with overweight children were more likely to purchase special foods for children and spend more money on these special foods. Previous studies found that Malawian parents in rural areas have a preference for packaged foods, like biscuits, Kamba puffs (a packaged snack food), and orange soda, over less processed, more nutrient dense alternatives [ 59 62 ]. Together with our findings, this suggests that behavior change communication interventions targeting feeding of “junk” foods to young children could be important for tackling the obesity epidemic in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to wealth, we use several other socioeconomic indicators that we interpret primarily as proxies for knowledge and preferences. Formal education, in particular has been shown to be a strong predictor of nutritional knowledge (Webb and Block, 2004, Schneider and Masters, 2019). We measure formal education as years of schooling of mothers and their partners (usually the father of the child).…”
Section: Theory Data and Methodsmentioning
confidence: 99%
“…Level of education, measured as years of schooling of the female spouse, is used to proxy nutritional knowledge. 22 , 23 We also include a dummy variable representing female-headed households, based on the research 24 which suggests that the nutrition sensitivity of household resource allocation is gender dependent.…”
Section: Datamentioning
confidence: 99%